Renal artery stenosis due to fibromuscular dysplasia in a transplanted kidney from a deceased donor: A difficult diagnosis at color doppler ultrasonography. Issue 2 (9th May 2013) - Venturini, M.; Querques, G.; Margari, S.; Agostini, G.; Colombo, M.; Caldara, R.; Socci, C.; De Cobelli, F.; Del Maschio, A.
ABSTRACT Atherosclerotic renal artery stenosis is a frequent cause of arterial hypertension and/or allograft dysfunction after kidney transplantation and is usually located at the iliac artery anastomosis. Fibromuscular dysplasia is a less frequent, nonatherosclerotic, vascular disease, inducing stenosis at the proximal/mid‐distal part of the renal artery. We report the case of a 44‐year‐old woman, in whom serum creatinine concentration increased and arterial hypertension developed 3 months after renal transplantation. Color Doppler ultrasonography showed a low arterial resistance index and prolonged acceleration time in the interlobar arteries, and a significantly increased peak systolic velocity at the mid third of the renal artery, demonstrating hemodynamically significant stenosis. Percutaneous transluminal angioplasty allowed stenosis correction and was followed by creatinine concentration and arterial blood pressure normalization. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound42:116–120, 2014